2013
DOI: 10.1590/s1415-43662013000600003
|View full text |Cite
|
Sign up to set email alerts
|

Cana-de-açúcar fertirrigada com vinhaça via irrigação por gotejamento subsuperficial em três ciclos de cana-soca

Abstract: RESUMOObjetivou-se, com esta pesquisa, avaliar o efeito da irrigação, da fertigação mineral e da vinhaça, aplicadas via irrigação por gotejamento subsuperficial, no número de perfilhos, produção de colmos, qualidade tecnológica e rendimento de açúcar recuperável, nos três primeiros ciclos de cana-soca. Os tratamentos foram: T1NI -Cultivo não irrigado com adubação mineral; T2I -Cultivo irrigado e fertirrigado com fertilizantes minerais; T3Iv -Cultivo irrigado e fertirrigado com a vinhaça suprindo o K e compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
5
0
4
Order By: Relevance
“…Under full irrigation conditions, in a study with 24 varieties, Maschio (2011) observed variation in the gross yield of sugar on the order of 19.5 to 27.5 t ha -1 , with lower values for the varieties RB855453 (22.0 t ha -1 ), CTC8 (21.6 t ha -1 ), RB925211 (20.6 t ha -1 ), CTC14 (20.4 t ha -1 ) and SP81-3250 (19.5 t ha -1 ). Barbosa et al (2013) reported mean sugar yield of 25.5 Mg ha -1 only in the cycle of the second ratoon cane under irrigated cultivation and vinasse application.…”
Section: Resultsmentioning
confidence: 99%
“…Under full irrigation conditions, in a study with 24 varieties, Maschio (2011) observed variation in the gross yield of sugar on the order of 19.5 to 27.5 t ha -1 , with lower values for the varieties RB855453 (22.0 t ha -1 ), CTC8 (21.6 t ha -1 ), RB925211 (20.6 t ha -1 ), CTC14 (20.4 t ha -1 ) and SP81-3250 (19.5 t ha -1 ). Barbosa et al (2013) reported mean sugar yield of 25.5 Mg ha -1 only in the cycle of the second ratoon cane under irrigated cultivation and vinasse application.…”
Section: Resultsmentioning
confidence: 99%
“…A aplicação da vinhaça através da fertirrigação é bastante difundida nas regiões canavieiras com resultados satisfatórios em relação às alterações químicas no solo, como o aumento de matéria orgânica, pH e teores de nutrientes totais (BEBÉ et al 2009 (TASSO JÚNIOR et al 2007, SINGH et al 2007, BARBOSA et al 2013), Brix (TASSO JÚNIOR et al 2007, SINGH et al 2007, BARBOSA et al 2012, BARBOSA et al 2013, fibra (OLIVEIRA et al 2009 ) e com cinco repetições, totalizando 20 unidades experimentais. Cada unidade experimental apresentava área de 24 m 2 (6 m x 4 m), em canavial de soca de segundo ano e terceiro corte, variedade RB 855453 de ciclo precoce, com espaçamento entre linhas de 1,5 m. O plantio da cana ocorreu no ano de 2008, utilizando preparo convencional do solo, que consistiu de uma subsolagem a 50 cm de profundidade seguida de duas gradagens pesadas e uma niveladora.…”
Section: Introductionunclassified
“…Regarding pol (apparent sucrose), the treatments influence follow the same behavior observed for TSS, i.e., there is no statistical variation of this variable as a function of the increased ozone concentration. Barbosa et al (2013) studied the fertirrigated sugarcane with vinasse via surface drip irrigation in three cane-stalk cycles and verified a variation in TSS and pol values with 225, 245 and 305 days after harvest. TSS results ranged from 18 to 19 °Brix with 225 days to 20 to 21 °Brix in 305 days.…”
Section: Resultsmentioning
confidence: 92%